2020
DOI: 10.14309/ctg.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Phosphodiesterase-5 Inhibitors and Colorectal Cancer in a National Cohort of Patients

Abstract: INTRODUCTION: To examine the association between phosphodiesterase-5 (PDE-5) inhibitor use and incidence of colorectal cancer among patients with erectile dysfunction treated in the Veterans Affairs (VA) Healthcare System. METHODS: A retrospective cohort study using the Veterans Affairs Informatics and Computing Infrastructure was conducted, with data spanning January 2001–December 2016. Patients were followed up from index until (i) the first diagnosis of colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A large body of work spanning two decades has highlighted cGMP-elevating PDE inhibitors for the prevention and treatment of colorectal cancer. Building on this foundation, recent largecohort retrospective epidemiological studies support their efficacy in humans, and provide the impetus for prospective clinical studies to interrogate their utility in patients (Huang et al, 2019;Sutton et al, 2020). However, there are inconsistencies in the literature regarding the potential utility of cGMP-PDE inhibitors as a primary prevention modality or as chemotherapy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work spanning two decades has highlighted cGMP-elevating PDE inhibitors for the prevention and treatment of colorectal cancer. Building on this foundation, recent largecohort retrospective epidemiological studies support their efficacy in humans, and provide the impetus for prospective clinical studies to interrogate their utility in patients (Huang et al, 2019;Sutton et al, 2020). However, there are inconsistencies in the literature regarding the potential utility of cGMP-PDE inhibitors as a primary prevention modality or as chemotherapy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PDE5 inhibitor use was associated with a significantly lower incidence of CRC (Figure 3; OR 0.85, CI 0.78–0.93, p < 0.001, I 2 = 52%). Three studies comprised 88.1% of the overall weighting of effect [22, 25, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, polyps formed in sildenafil-treated mice showed greater differentiation, less proliferation, less inflammation, little infiltration of myeloid cells as well as a reduction in the expression of pro-inflammatory factors such as INFg and IL-6 (71). In a study of 192,661 patients, the use of PDE5 inhibitors was shown to be associated with a decreased risk of developing colon cancer (72).…”
Section: Colorectal Cancermentioning
confidence: 99%